MECHANISMS OF PUBLIC GOVERNANCE OF COMMUNITY SOCIAL CAPITAL CONSIDERING ECONOMIC REGULATION OF THE FISHERIES SECTOR DEVELOPMENT AND EMERGENCY CHALLENGES - VDOVENKO, Nataliia; SYZON, Volodymyr; TYSHECHKO, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proposes theoretical and applied foundations for implementing public governance mechanisms for managing the social capital of communities, considering the specific features of economic regulation in the fisheries sector. This aims to identify institutional barriers, explore the potential for circular economy models, and integrate digital and social innovations into local governance practices. Contemporary transformational processes in public administration prompt scholars to reassess the role of social capital as a foundational resource for community development, particularly in sectors of strategic importance for food security, employment, and spatial economy, especially in fisheries. Social capital, encompassing trust, social networks, horizontal ties, and collective action readiness, serves as a cornerstone for enhancing the effectiveness of public policy, particularly at the local level, where decentralized governance practices are gaining importance. At the same time, the fisheries sector, as a component of Ukraine’s "blue economy," has the potential to become a source of economic activity and a platform for developing new models of social interaction at the local level. The complexity and interdisciplinary nature of the topic stem from the need to combine tools of public governance, economic regulation, and institutional support to foster an enabling environment for the development of the fisheries industry and the strengthening of social capital in communities. The developed theoretical and applied model of public governance for fisheries development in communities under extraordinary challenges, considering martial law, economic turbulence, and climate risks, demonstrates the relevance of integrating digital tools, social innovations, and economic regulation to improve decision-making effectiveness. Emphasis is placed on involving veterans in aquaculture employment, facilitating social reintegration, and forming new social capital. Evaluating the model’s effectiveness enables comparisons across communities based on measurable impact indicators. In the long term, such a model may serve as a foundation for shaping national policies in the field of the blue economy, grounded in the principles of inclusivity, circularity, and decentralization. It is noted that post-war recovery conditions, the impact of climate change, and technological advancement will contribute to forming a new system of public governance of social capital at the local level. In the fisheries sector, communities act as consumers and initiators of systemic transformations, capable of forecasting their own development through economic incentives and digital tools.